Species Diversity of Understory Vegetation of Riparian Zone of Upper Ranoyapo River, South Minahasa, North Sulawesi - Wanindi, Agustina; Siahaan, Ratna; Nio, Song Ai (Universitas Sam Ratulangi, 2025)
Riparian is a transitional ecosystem that occupies the area between land and river water bodies. The study aimed to analyze the diversity of understory vegetation of riparian zone of the Ranoyapo River upstream at Kinamang Village and Kinamang Satu Village, South Minahasa Regency. Vegetation samples were taken at two stations, namely Station I at Kinamang Village before the Ranoyapo dam and Station II in Kinamang Satu Village after dam. The purposive sampling method was used with quadrat plot vegetation analysis. Data analysis was carried out descriptively. Understory vegetation found in the riparian zone of the Ranoyapo River upstream amounted to 16 species, namely Acmella paniculata, Arenga pinata, Aglaonema simplex, Colocasia esculenta var. esculenta, Diospyros abyssinica, Diplazium esculentum, Diplazium sp., Elatostema stewardii, Ficus septica, Homalomena sp., Hellenia speciosa, Musa paradisiaca, Pandanus amaryllifolius, Phrynium pubinerve, Piper sp., and Selaginella obtusa. The diversity index of riparian vegetation understory vegetation at Station I and Station II were 1.76 and 1.95, respectively were classified as moderate diversity. This indicated that there was ecological pressure on the riparian understory vegetation of the upstream Ranoyapo River.